2020
DOI: 10.1002/jmv.26035
|View full text |Cite
|
Sign up to set email alerts
|

Increase in COVID‐19 cases and case‐fatality and case‐recovery rates in Europe: A cross‐temporal meta‐analysis

Abstract: The new coronavirus (COVID-19) infection reported in China in December 2019 has become a pandemic in a few weeks, affecting the entire world. In this respect, it is crucial to determine the case-increase, case-fatality, and case-recovery rates to control COVID-19. In this study, the case-increase, case-fatality, and case-recovery rates of COVID-19 in 36 European countries were analyzed with the meta-analysis method using data released by the health organizations and WHO. The data were obtained from the website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 17 publications
3
55
0
2
Order By: Relevance
“…We found an extremely low prevalence of SARS-CoV-2 seropositivity in Bonn, a middle-large city in the western part of Germany with a relatively low burden of COVID-19, both regionally and internationally. 16,17 In addition, we found that: Our findings also confirm that limited exposure of the local population to SARS-CoV-2 most likely accounts for the relatively low rates of regional COVID-19-related hospitalizations and mortality, supporting the efficacy of early implementation of social distancing and confinement measures in Germany. 16,17 The current seroprevalence estimates are lower than the two other German community-based serosurveys.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We found an extremely low prevalence of SARS-CoV-2 seropositivity in Bonn, a middle-large city in the western part of Germany with a relatively low burden of COVID-19, both regionally and internationally. 16,17 In addition, we found that: Our findings also confirm that limited exposure of the local population to SARS-CoV-2 most likely accounts for the relatively low rates of regional COVID-19-related hospitalizations and mortality, supporting the efficacy of early implementation of social distancing and confinement measures in Germany. 16,17 The current seroprevalence estimates are lower than the two other German community-based serosurveys.…”
Section: Discussionsupporting
confidence: 76%
“…16,17 In addition, we found that: Our findings also confirm that limited exposure of the local population to SARS-CoV-2 most likely accounts for the relatively low rates of regional COVID-19-related hospitalizations and mortality, supporting the efficacy of early implementation of social distancing and confinement measures in Germany. 16,17 The current seroprevalence estimates are lower than the two other German community-based serosurveys. 14,15 However, both these previous serosurveys were conducted in communities following super-spreading events, and are unlikely to reflect the state of other regions in Germany with relatively low COVID-19 burden.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The spectrum of clinical manifestations of COVID-19 can vary from a mild respiratory syndrome to an Acute Respiratory Distress Syndrome (ARDS) requiring mechanical ventilation [ [12] , [13] , [14] , [15] ], where older age and comorbidities increase the risk of a more severe disease [ 16 , 17 ]. Case fatality rate has been reported to be around 4–4.5%, anyway varying widely among different countries and different testing strategies [ [18] , [19] , [20] ]. Up to date, only remdesivir and dexamethasone proved to be effective in clinical trials: remdesivir shortened the length of hospitalization, anyway without a meaningful impact on mortality [ 21 ], while dexamethasone significantly reduced mortality in patients requiring supplemental oxygen [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such increase was paralleled by an increase in mortality from 9.5% in March to 12.1% afterwards [6] . In a recent meta-analysis of data gathered from 36 European countries [7] , the case-fatality rate of patients with COVID-19 progressively rose from 1.5% in the week subsequent to the first death to 6.5% at the sixth week, with an average case-fatality of 4.5%. However, the meta-analysis could not adjust for the changes in the clinical characteristics of subjects across the different Countries over the examined time period [7] .…”
mentioning
confidence: 99%